2021
DOI: 10.3390/jcm10112320
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and Risks of Antiviral Treatment during Pregnancy in Patients with Chronic Hepatitis B

Abstract: Hepatitis B virus (HBV) is a main cause of chronic liver disease worldwide and can lead to severe liver diseases. The World Health Organization has planned to eliminate viral hepatitis, including hepatitis caused by HBV and hepatitis C virus, by 2030. As mother-to-child transmission (MTCT) of HBV is a main cause of chronic HBV infection, MTCT prevention is the main target to reduce the risk of chronic HBV infection and eliminate the disease. Recent clinical trials and meta-analyses found that antiviral therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 84 publications
0
6
0
Order By: Relevance
“…The risk of intrauterine infections can be reduced if the mother receives antiviral therapy during pregnancy [ 24 , 34 ], prompting the WHO to recommend the administration of tenofovir in the third trimester of pregnancy until at least birth in pregnant women with high viral load, i.e.load 200,000 IU/mL (equivalent to 10 6 copies/mL) [ 35 ]. In resource-limited countries, WHO recommends using HBeAg as an alternative to viral quantification.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of intrauterine infections can be reduced if the mother receives antiviral therapy during pregnancy [ 24 , 34 ], prompting the WHO to recommend the administration of tenofovir in the third trimester of pregnancy until at least birth in pregnant women with high viral load, i.e.load 200,000 IU/mL (equivalent to 10 6 copies/mL) [ 35 ]. In resource-limited countries, WHO recommends using HBeAg as an alternative to viral quantification.…”
Section: Discussionmentioning
confidence: 99%
“…The increasing number of mothers were receiving early medical treatment and regular prenatal examinations. Therefore, the risk of liver failure or MTCT (mother-to-child transmission) is signi cantly reduced 9,37 .…”
Section: Discussionmentioning
confidence: 99%
“…Most studies found that nucleoside analog therapy in late pregnancy, followed by treatment withdrawal early postpartum, was associated with ALT flare; however, they reported variable changes in HBV DNA levels or rates of HBeAg seroconversion during immediate postpartum up to 1 year of follow-up [ 8 , 11 , 14 16 ]. The definition of a hepatitis flare varies according to the literature [ 7 , 17 , 18 ], but a significant increase in serum ALT levels from the baseline level or higher than ULN is generally defined as ALT flare [ 10 ]. In this observational study, the rate of postpartum ALT flare was 69%.…”
Section: Discussionmentioning
confidence: 99%